Dynamics of pertussis toxin IgG after symptomatic pertussis in children and adults. Issue 16 (3rd April 2020) - Jõgi, Piia; Soeorg, Hiie; Oona, Marje; Kaart, Tanel; Toompere, Karolin; Maskina, Tereza; Koort, Iris; Rätsep, Anneli; Lutsar, Irja; ,
Highlights: The peak of the PT-IgG is higher in adults than in children. Time to reach the peak of the PT-IgG level longer in adults than in children. The decrease of the PT-IgG is faster in adults than in children. 1 year post pertussis 50% of children and 25% of adults had PT-IgG at least 100 IU/mL. The uniform diagnostic cut-off point of the PT-IgG may not suit to all age groups. Abstract: Background and aim: The knowledge of dynamics of pertussis toxin (PT)-IgG after pertussis and the appropriate diagnostic cut-off value is limited. We aimed to describe the dynamics of PT-IgG in children and adults up to three years after symptomatic pertussis. Methods: Patients with persistent cough of unknown aetiology were prospectively enrolled 2012–2014. Pertussis was confirmed by culture, PCR and/or serology. The follow-up samples were taken 4–6 weeks, 1, 2 and 3 years after enrolment. PT-IgG kinetics was described by biexponential model. Results: Pertussis was diagnosed in 22 patients [median (IQR) age 17.7 (8.4–38.6) years]. Adults compared with children had higher peak of the PT-IgG 397 (IQR 374–518) vs 292 (200–363), p = 0.007, longer time to reach peak PT-IgG 16.4 (IQR 15.6–16.8) days vs 13.3 (13.2–13.4) days, p=<0.001 and shorter PT-IgG half-life 24 days (IQR 20–40) and 364 days (IQR 359–486 ) p < 0.001. Conclusion: After symptomatic pertussis, adults and children have different dynamics of PT-IgG. Clinical trial registry: Not applicable.